Upaya Meningkatkan Keterampilan Membaca dalam Menemukan Informasi pada Teks Panjang melalui Metode Scanning pada Siswa Kelas Iii Sd Negeri 1 Menteng - Muhammad Rezeki; Yuarina Eka Friskilla; Agnes Agnes; Kevin F Imanuel; M Faisal Riza; Yunanie Yunanie (Simpati, 2026)
This Classroom Action Research (CAR) aimed to improve the ability of third-grade students at SDN 5 Menteng Palangka Raya to identify information in long texts through the application of the scanning method. The ability to locate information quickly and accurately is an essential reading skill that supports literacy development among elementary school students. The study was conducted in two cycles involving 10 third-grade students as research participants. Each cycle consisted of planning, action implementation, observation, and reflection stages. Research data were collected through observations of learning implementation and students’ reading skill assessments. The findings revealed that the application of the scanning method successfully improved both the learning process and student learning outcomes. The implementation of learning activities increased from 85% in Cycle I to 97% in Cycle II. In addition, the average reading skill score improved significantly from 70 in Cycle I to 94 in Cycle II. These results indicate that students became more proficient in identifying important information in long texts quickly and accurately. Therefore, the scanning method proved to be effective in enhancing reading skills and literacy among elementary school students. The method can be considered an alternative instructional strategy for improving reading comprehension and information-finding skills in elementary education.